**Correct option is (C) 12**

Let the age of mother be x years and

age of her son be y years.

12 years ago, the mother age was (x - 12) years

14 years ago, the mother age was (x - 14) years

9 years hence, the mother's age will be (x+9) years

and her son's age will be (y+9) years

According to given conditions, we have

x+y = 2 (x - 12)

\(\Rightarrow\) x+y = 2x - 24

\(\Rightarrow\) y = x - 24 ______________(1)

And (x+9) + (y+9) = 3 (x - 14)

\(\Rightarrow\) x + y + 18 = 3x - 42

\(\Rightarrow\) x + x - 24 + 18 = 3x - 42

\(\Rightarrow\) 2x - 6 = 3x - 42

\(\Rightarrow\) 2x - 3x = 6 - 42

\(\Rightarrow\) -x = -36

\(\Rightarrow\) x = 36

\(\therefore\) y = 36 - 24 = 12 (From (1))

Hence, her son’s present age is 12 years.